Negative electrode material of low-temperature-resistant high-rate long-cycle battery and preparation process of negative electrode material

By using a combination of micron silicon powder, graphite powder and binder in the negative electrode material of the battery, and using continuous stirring, extrusion molding and high-temperature heat treatment processes, a silicon-carbon composite material with network-like pores is formed, which solves the structural damage caused by volume changes in the silicon material during lithium embedding and deliquification, and significantly improves the battery's charge and discharge efficiency and cycle stability performance.

CN119650625APending Publication Date: 2025-03-18HUIZHOU WES NEW ENERGY LIMITED
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411727191.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The violent expansion of silicon material during lithium embedding and the violent contraction during deliquency leads to structural cracking, powdering and reduced battery cycle stability, and it is difficult to form a stable solid electrolyte interface film in the electrolyte, resulting in attenuation of battery capacity.

Method used

A combination of micron silicon powder, graphite powder and binder is used to form a silicon-carbon composite material with network pores through continuous stirring, extrusion molding and high-temperature heat treatment processes to alleviate the volume expansion effect of the silicon material.

Benefits of technology

It significantly improves the charge and discharge efficiency and cycle stability performance, reduces production costs and improves production efficiency, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650625A_ABST
    Figure CN119650625A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, in particular to a negative electrode material of a low-temperature-resistant high-rate long-cycle battery and a preparation process of the negative electrode material, the production efficiency is improved through a continuous production process, the production cost is reduced, the technical process is stable, the product quality is uniform, the performance is reliable, and the negative electrode material is suitable for large-scale production. Through process design, the rod-shaped silicon-carbon composite material extruded by an extruder can inhibit volatilization of asphalt to a certain extent, carbides generated in the carbonization process of the asphalt can become a pore-forming agent, and various uniform network-shaped pores are formed in the rod-shaped interior, namely the surfaces of micron silicon and graphite; in this way, the micron silicon is located under a coating layer with a plurality of pores, and the pores can better relieve the volume expansion effect of the micron silicon in the prior art, so that the first charge-discharge efficiency and the cycle stability are greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of battery materials, and in particular to a negative electrode material for a low-temperature resistant, high-rate, long-cycle battery and a preparation process thereof. Background Art

[0002] At present, silicon materials have become a new generation of negative electrode materials. However, the volume of silicon materials will expand dramatically when lithium is inserted, resulting in a volume expansion effect, and will shrink dramatically when lithium is removed. This repeated and drastic volume change will cause the silicon material to crack and pulverize, resulting in structural collapse, causing the active material to peel off from the current collector and lose electrical contact, reducing the battery cycle stability. In addition, due to this volume effect, it is difficult for silicon to form a stable solid electrolyte interface film (SEI) in the electrolyte. As the structure is destroyed, new silicon is exposed on the surface and continuously forms an SE I film, which will aggravate the corrosion of silicon, thereby causing the battery capacity to decay. At the same time, the existing preparation processes for silicon-carbon negative electrode materials are mostly intermittent production, with low production efficiency and high cost, and it is difficult to meet the needs of large-scale production. Summary of the invention

[0003] In order to solve the above technical problems, the present application provides a negative electrode material for a low-temperature resistant, high-rate, long-cycle battery, comprising micron silicon powder, graphite powder and a binder, wherein the content of the micron silicon powder is 10%-30%, the content of the graphite powder is 65%-89%, and the content of the binder is 1%-5%.

[0004] Preferably, the binder is a mixture of coal-based asphalt and oil-based asphalt.

[0005] Preferably, a preparation process for preparing the above-mentioned negative electrode material comprises the following steps:

[0006] S1: Mix micron silicon powder and graphite powder, stir them through a continuous stirring device, pour the mixed materials into a fusion machine continuously and add a binder, process for 25-30 minutes, and obtain a uniform mixed material;

[0007] S2: continuously feeding the mixed material into an extruder, and extruding it under a certain temperature and pressure to form a continuous silicon-carbon composite material rod;

[0008] S3: continuously feeding the silicon-carbon composite material rods into a high-temperature furnace for heat treatment under an inert atmosphere to cause the material to react and crystallize;

[0009] S4: Cutting and crushing the heat-treated silicon-carbon composite material rods to obtain silicon-carbon negative electrode materials of required particle size.

[0010] Preferably, in step S1, the micron silicon powder and graphite powder are first dried at a temperature of 80-120° C. for a drying time of 2-4 hours.

[0011] Preferably, in step S1, the stirring speed of the stirring device is 50-200 rpm, the stirring time is 1-3 hours, the stirring temperature is 30-50°C, the speed of the fusion machine is 500-700 rpm, and the duration is 1-2 hours.

[0012] Preferably, in step S2, the extrusion temperature of the extruder is generally 200-250°C, the extrusion pressure is 5-20 MPa, and the extrusion speed is 1-5 m / min.

[0013] Preferably, in step S3, the high temperature furnace is heated to 800-1200°C at a heating rate of 25°C / min and kept at this temperature for 8-15 hours, and the inert gas is nitrogen or argon.

[0014] Preferably, in step S4, the cutting speed is 5-20 mm / min, the cutting length is 10-50 mm, and the diameter is 5-10 mm.

[0015] Preferably, the micron silicon powder preparation process is:

[0016] A1. Adding an organic solvent to silicon powder to obtain silicon powder slurry, wherein the solid content of the silicon powder slurry is configured to be 20-25%, grinding the silicon powder slurry, then performing ultrasonic treatment while stirring, and then spray drying to obtain micron silicon powder;

[0017] A2. Add micron silicon powder to 2-4% hydrofluoric acid solution and let it stand for 10 minutes. Take out the micron silicon powder and wash it with deionized water. Dry the silicon carbide carbon microspheres in a vacuum environment at 80° C. to obtain micron silicon powder with micropores.

[0018] Preferably, in a battery, the negative electrode material is a silicon-carbon negative electrode material prepared by the above-mentioned preparation process.

[0019] From the above, it can be seen that the following beneficial effects can be obtained by applying the method provided by this application:

[0020] 1. The continuous production process improves production efficiency, reduces production costs, has a stable process, uniform product quality, reliable performance, and is suitable for large-scale production.

[0021] 2. Through process design, the silicon-carbon composite material extruded into a rod shape by the extruder will inhibit the volatilization of asphalt to a certain extent. The carbide produced during the carbonization process of asphalt will become a pore-forming agent, and various uniform network pores will be formed inside the rod, that is, on the surface of micron silicon and graphite. In this way, the micron silicon is under a coating layer with many pores. These pores can better alleviate the volume expansion effect of micron silicon in the existing technology, thereby greatly improving the initial charge and discharge efficiency and cycle stability performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the description of the embodiments of the present application or the prior art are briefly introduced below. Obviously, the drawings described below are only part of the embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor.

[0023] Figure 1 This is a flowchart of the process for preparing the negative electrode material of the low temperature resistant, high rate and long cycle battery of the embodiment of the present application;

[0024] Figure 2 This is a cycle number diagram of a low temperature resistant, high rate, long cycle battery according to an embodiment of the present application;

[0025] Figure 3 The capacity and voltage of the low-temperature resistant, high-rate, long-cycle battery of the embodiment of the present application at different discharge rates;

[0026] Figure 4 This is a discharge curve diagram of the low-temperature-resistant, high-rate, long-cycle battery at -40°C according to an embodiment of the present application. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0028] Example

[0029] In order to solve the above technical problems, this embodiment provides a negative electrode material for a low temperature resistant, high rate and long cycle battery and a preparation process thereof, such as Figure 1 As shown, the following steps are included:

[0030] S1: Mix micron silicon powder and graphite powder, stir them through a continuous stirring device, pour the mixed materials into a fusion machine and add a binder, process for 25-30 minutes, and obtain a uniform mixed material;

[0031] Specifically, the content of micron silicon powder is 10%-30%, the content of graphite powder is 65%-89%, and the content of binder is 1%-5%. Preferably, the content of micron silicon powder is 30%, the content of graphite powder is 65%, the content of binder is 5%, and the binder is a mixture of coal-based asphalt and oil-based asphalt.

[0032] Furthermore, the micron silicon powder and graphite powder are first dried, and the micron silicon powder and graphite powder are put into a dryer according to a proportion, the drying temperature is 80-120° C., and the drying time is 2-4 hours.

[0033] The dried micron silicon powder and graphite powder are put into a stirring device and stirred by a continuous stirring device at a stirring speed of 50-200 rpm, a stirring time of 1-3 hours, and a stirring temperature of 30-50°C. The mixed material is then poured into a fusion machine and a binder is added, and the mixture is processed for 25-30 minutes to obtain a uniform mixed material, wherein the rotation speed of the fusion machine is 500-700 rpm and the duration is 1-2 hours.

[0034] In this step, the micron silicon powder preparation process is:

[0035] A1. Add an organic solvent to silicon powder to obtain silicon powder slurry, the solid content of the silicon powder slurry is configured to be 20-25%, grind the silicon powder slurry, then perform ultrasonic treatment while stirring, and then spray dry to obtain micron silicon powder; by adding an organic solvent to the silicon powder, the silicon powder can be prevented from being oxidized during the grinding process. In this embodiment, the organic solvent is anhydrous ethanol. The solid content of the silicon powder slurry is configured to be 20%, so that the organic solvent can ensure the anti-oxidation effect of the silicon powder while ensuring sufficient grinding. Ordinary silicon can be ground into micron silicon powder by using a solvent-type closed ball milling device, which can inhibit the oxidation of silicon powder during the ball milling process.

[0036] A2. Add micron silicon powder to 2-4% hydrofluoric acid solution and let it stand for 10 minutes. Take out the micron silicon powder and wash it with deionized water. Dry the silicon carbide carbon microspheres in a vacuum environment at 80° C. to obtain micron silicon powder with micropores.

[0037] In the process of preparing micron silicon powder, micron silicon powder with micropores is prepared through etching with hydrofluoric acid solution, which can alleviate the problem of silicon powder volume expansion. Then the micron silicon powder is stirred and mixed with graphite powder, so that the graphite powder fills and covers the micron silicon powder with micropores. The mixed materials are poured into a fusion machine and a binder is added. The binder is a mixture of coal-based asphalt and oil-based asphalt. Through the fusion machine, the micron silicon powder and graphite powder are wrapped by the porous amorphous carbon formed by the volatilization of asphalt, and are evenly distributed with many pores.

[0038] S2: continuously feeding the mixed material into an extruder, and extruding it under a certain temperature and pressure to form a continuous silicon-carbon composite material rod;

[0039] The discharge end of the fusion machine in step S1 is connected to the extruder through a transmission pipeline, and the mixed material obtained in step S1 is directly transported to the extruder for extrusion molding. The extrusion temperature of the extruder is generally 200-250°C, the extrusion pressure is 5-20MPa, and the extrusion speed is 1-5 meters per minute. Preferably, the extrusion pressure is 15MPa and the extrusion speed is 4 meters per minute. During the extrusion process, the extrusion parameters are designed to ensure continuous extrusion and molding of the material, while avoiding problems such as uneven extrusion and blockage.

[0040] Furthermore, the silicon-carbon composite material extruded into a rod shape by an extruder will inhibit the volatilization of asphalt to a certain extent. The carbide produced during the carbonization process of the asphalt will become a pore-forming agent, forming various uniform network pores inside the rod, that is, on the surface of micron silicon and graphite. In this way, the micron silicon is under a coating layer with many pores. These pores can better alleviate the volume expansion effect of micron silicon in the existing technology, thereby greatly improving the initial charge and discharge efficiency and cycle stability performance.

[0041] S3: continuously feeding the silicon-carbon composite material rods into a high-temperature furnace for heat treatment under an inert atmosphere to cause the material to react and crystallize;

[0042] The silicon-carbon composite material rod obtained in step S2 is continuously fed into a high-temperature furnace. In step S3, the heat treatment can be carried out in a tubular furnace or a box furnace. The high-temperature furnace is heated to 800-1200°C at a heating rate of 25°C / min and kept warm for 8-15 hours. The inert gas is nitrogen or argon. During the high-temperature heat treatment process, chemical reactions and crystallizations will occur between silicon powder and graphite powder to form a special structure of silicon-carbon composite materials. This structure can improve the conductivity, capacity, and cycle stability of the material. At the same time, the continuous production process improves production efficiency, reduces production costs, and is suitable for large-scale production.

[0043] S4: Cutting and crushing the heat-treated silicon-carbon composite material rods to obtain silicon-carbon negative electrode materials of required particle size.

[0044] In step S4, the cutting speed is 5-20 mm / min, the cutting length is 10-50 mm, and the diameter is 5-10 mm. The cutting speed ensures that the cutting surface is smooth, free of cracks, burrs and other defects. The rod is then crushed by a crushing device. The crushing device can be a ball mill or a jet mill, which can crush the cut rod into powder of the required particle size. The crushing time of the crushing device is 2-6 hours, the crushing temperature is between 20-50°C, the humidity is controlled between 30-50%, and the particle size of the crushed rod is controlled between 5-30um.

[0045] This embodiment provides a battery, wherein the negative electrode material is the silicon-carbon negative electrode material obtained by the above-mentioned preparation method. The battery is subjected to discharge and cycle tests. Figure 2 is the number of cycles of the battery, such as Figure 3 is the capacity and voltage of the battery at different discharge rates.

[0046] This embodiment provides a reference group, and the preparation process of the silicon-carbon negative electrode material includes the following steps:

[0047] S1: ordinary silicon powder, graphite powder and binder are mixed according to proportion, and stirred by a continuous stirring device to obtain a uniform mixed material;

[0048] S2: continuously feeding the mixed material into an extruder, and extruding it under a certain temperature and pressure to form a continuous silicon-carbon composite material rod;

[0049] S3: continuously feeding the silicon-carbon composite material rods into a high-temperature furnace for heat treatment under an inert atmosphere to cause the material to react and crystallize;

[0050] S4: Cutting and crushing the heat-treated silicon-carbon composite material rods to obtain silicon-carbon negative electrode materials of required particle size.

[0051] The reference group does not grind the ordinary silicon powder, but directly mixes the silicon powder, graphite powder and binder, then extrudes them into a shape, heat treats them in an inert atmosphere, cuts and crushes them to obtain the silicon-carbon negative electrode material, and then uses the silicon-carbon negative electrode material to prepare batteries. Figure 4 As shown, the discharge curves of the batteries of the reference group and the experimental group of the embodiment of the present invention at -40°C are shown in FIG. Figure 4 It can be seen that the battery prepared by the silicon-carbon negative electrode material obtained in the experimental group of this embodiment has better discharge performance at low temperature than ordinary silicon-carbon negative electrode materials.

[0052] The above-described implementation methods do not constitute a limitation on the protection scope of the technical solution. Any modification, equivalent replacement and improvement made within the spirit and principle of the above-described implementation methods shall be included in the protection scope of the technical solution.

Claims

1. A negative electrode material for a low temperature resistant, high rate and long cycle battery, characterized in that: The invention comprises micron silicon powder, graphite powder and a binder. The content of the micron silicon powder is 10%-30%, the content of the graphite powder is 65%-89%, and the content of the binder is 1%-5%.

2. The negative electrode material for a low temperature resistant, high rate and long cycle battery according to claim 1, characterized in that: The binder is a mixture of coal-based asphalt and oil-based asphalt.

3. A preparation process, characterized in that: The method for preparing the negative electrode material according to claim 1-2 comprises the following steps: S1: Mix micron silicon powder and graphite powder, stir them through a continuous stirring device, pour the mixed materials into a fusion machine continuously and add a binder, process for 25-30 minutes, and obtain a uniform mixed material; S2: continuously feeding the mixed material into an extruder, and extruding it under a certain temperature and pressure to form a continuous silicon-carbon composite material rod; S3: continuously feeding the silicon-carbon composite material rods into a high-temperature furnace for heat treatment under an inert atmosphere to cause the material to react and crystallize; S4: Cutting and crushing the heat-treated silicon-carbon composite material rods to obtain silicon-carbon negative electrode materials of required particle size.

4. The preparation process according to claim 3, characterized in that: In step S1, the micron silicon powder and graphite powder are first dried at a temperature of 80-120° C. for a drying time of 2-4 hours.

5. The preparation process according to claim 3, characterized in that: In step S1, the stirring speed of the stirring device is 50-200 rpm, the stirring time is 1-3 hours, the stirring temperature is 30-50°C, the speed of the fusion machine is 500-700 rpm, and the duration is 1-2 hours.

6. The preparation process according to claim 3, characterized in that: In step S2, the extrusion temperature of the extruder is generally 200-250°C, the extrusion pressure is 5-20 MPa, and the extrusion speed is 1-5 m / min.

7. The preparation process according to claim 3, characterized in that: In step S3, the high temperature furnace is heated to 800-1200°C at a heating rate of 25°C / min and kept at this temperature for 8-15 hours, and the inert gas is nitrogen or argon.

8. The preparation process according to claim 3, characterized in that: In step S4, the cutting speed is 5-20 mm / min, the cutting length is 10-50 mm, and the diameter is 5-10 mm.

9. The preparation process according to claim 1, characterized in that: The micron silicon powder preparation process is as follows: A1. Adding an organic solvent to silicon powder to obtain silicon powder slurry, wherein the solid content of the silicon powder slurry is configured to be 20-25%, grinding the silicon powder slurry, then performing ultrasonic treatment while stirring, and then spray drying to obtain micron silicon powder; A2. Add micron silicon powder to 2-4% hydrofluoric acid solution and let it stand for 10 minutes. Take out the micron silicon powder and wash it with deionized water. Dry the silicon carbide carbon microspheres in a vacuum environment at 80° C. to obtain micron silicon powder with micropores.

10. A battery, characterized in that: The negative electrode material is a silicon-carbon negative electrode material prepared by the preparation process of any one of claims 3-9.

Citation Information

Patent Citations

  • High-performance silicon-carbon cathode material and preparation method thereof

    CN107785560A

  • Silicon-carbon anode material for lithium ion battery and preparation method thereof

    CN111725504A

  • Lithium ion battery silicon-carbon composite negative electrode material and preparation method thereof

    CN113363442A